Analysis of the Implementation of Activity Based Costing to Increase Cost Efficiency at Hotel Mel's in Manado - Tesya Sisilia Lupa; Natalia Y. T. Gerungai; Priscilia Weku (PT FORMOSA CENDEKIA GLOBAL, 2023)
Activity Based Costing is a system of accumulating costs and assigning costs to products using various cost drivers, carried out by tracing costs from activities and after that tracing costs from activities to products. The aim of this research is to find out how to apply activity based costing to increase cost efficiency at the Mel's Inn Manado Hotel. The data analysis method used in this research is the descriptive analysis method. Based on the research results obtained, the basic price of the room is a nominal value that is smaller than that determined by the hotel management. With a lower HPP for each room, it can be seen that the cost of goods sold has the lowest difference for the superior room type, this is because the amount of labor used is more than the working hours for other room types